German literature and the First World War the anti-war tradition : collected essays by Brian Murdoch - Murdoch, Brian 1944- (Ashgate studies in First World War history, 2015)
"The period immediately following the end of the First World War witnessed an outpouring of artistic and literary creativity, as those that had lived through the war years sought to communicate their experiences and opinions. In Germany this manifested itself broadly into two camps, one condemning the war outright; the other condemning the defeat. Of the former, Erich Maria Remarque's 'All Quiet on the Western Front' remains the archetypal example of an anti-war novel, and one that has become synonymous with the Great War. Yet the tremendous and enduring popularity of Remarque's work has to some extent eclipsed a plethora of other German anti-war writers, such as Hans Chlumberg, Ernst Johannsen, and Adrienne Thomas. In order to provide a more rounded view of German anti-war literature, this volume offers a selection of essays published by Brian Murdoch over the past twenty years"-- Provided by publisher